2022
DOI: 10.1111/gwat.13178
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Open Pit Mine Closure with Managed Aquifer Recharge

Abstract: Dewatering of open pit mines can lower the regional water table for distances of several kilometers from the pit. When the mine is closed, dewatering operations usually cease, and the water table near the pit begins to rise. If the pit is backfilled, the water table will eventually recover, but this recovery may take several hundred years. However, if the extracted water is re-injected into the subsurface, then this may accelerate recovery of the water table. We show that there is an optimal distance for re-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…In general, it is an unsuccessful management option under highly transmissive aquifer settings, as any gain in lake level quickly dissipates into the surrounding aquifer. It could be speculated, that managed aquifer recharge may have a role in rapid recovery of groundwater levels in mining regions of higher aquifer transmissivity (Cook et al 2022). In less permeable geology, added surplus water is retained much longer within the pit and elevated lake and groundwater levels as a result may last for several decades.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is an unsuccessful management option under highly transmissive aquifer settings, as any gain in lake level quickly dissipates into the surrounding aquifer. It could be speculated, that managed aquifer recharge may have a role in rapid recovery of groundwater levels in mining regions of higher aquifer transmissivity (Cook et al 2022). In less permeable geology, added surplus water is retained much longer within the pit and elevated lake and groundwater levels as a result may last for several decades.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on climate and hydrogeological conditions, the recovery may take tens to several hundreds of years. Cook et al (2022) found that groundwater recovery post‐mine closure may be enhanced by optimizing re‐injection distances from the pit so that injected water flows back to the closed pit soon after mining and dewatering operations have ceased. Water management post‐ closure is one of the most important aspects of environmental protection, and effective water management strategies during the mining process can significantly reduce the costs associated with rehabilitation (El Idrysy and Connelly 2012).…”
Section: Challenges and Opportunities For Mar In Miningmentioning
confidence: 99%
“…Effective groundwater management strategies are essential for open pit mines operating below the water table. Dewatering of open‐pit or underground mine workings is implemented to create dry conditions for mining operations (Rozkowski et al 2021; Cook et al 2022). This process creates a cone of depression, where water levels decrease around the mine, resembling the shape of an inverted cone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations